Cloning of Japanese Quail (Coturnix japonica) Follistatin and Production of Bioactive Quail Follistatin288 in Escherichia coli - Maaeni, Yusuf Mohammed; Lee, Sang Beum; Choi, Dong Hyuck; Mozdziak , Paul E.; Kim, Yong Soo (International Journal of Poultry Science, 2017)
Background and Objective: Follistatin (FST) is a cysteine-rich autocrine glycoprotein and plays an important role in mammalian prenatal and postnatal development. The FST binds to and inhibits myostatin (MSTN), a potent negative regulator of skeletal muscle growth, thus FST abundance enhances muscle growth in animals. The objective of this study was to determine cDNA sequence of quail FST and to produce biologically active quail FST288 (qFST288) in an Escherichia coli (E. coli) expression system. Materials and Methods: Total RNA isolated from quail ovary tissue was used in performing 3'-and 5'-RACE to determine the full-length mRNA sequence of quail FST. The full-length quail FST cDNA consisted of 1118 bp with an open reading frame (ORF) of 1032 bp. The qFST amino acid sequence deduced from qFST cDNA was identical to chicken FST except the sequence at 28 position. To produce recombinant qFST288 protein, Gibson assembly cloning method was used to insert the DNA fragments of qFST288 into pMALc5x vector downstream of the maltose-binding protein (MBP) gene and the plasmids containing the inserts were eventually transformed into shuffle E. coli strain for protein expression. Results: Soluble expression of the qFST288 protein was achieved through the experiments and the protein could be easily purified by the combination of amylose and heparin resin affinity chromatography. In an in vitro reporter gene assay, MBP-qFST288 demonstrated its capacity to suppress the activities of MSTN or activin A. Conclusion: Through cloning of quail FST cDNA, it was discovered that amino acid sequence of quail FST is identical to that of chicken FST. In addition, it was demonstrated that bioactive qFST288 could be produced in E. coli.